"Repellent Effect of Extracts and Essential Oils of Citrus limon (Rutaceae) and Melissa officinalis (Labiatae) Against Main Malaria Vector, Anopheles stephensi (Diptera: Culicidae)" - "MA Oshaghi; R Ghalandari; H Vatandoost; M Shayeghi; M Kamali-nejad; H Tourabi-Khaledi; M Abolhassani; M Hashemzadeh" (Tehran University of Medical Sciences, 2003)
Repellet effect of extracts and essential oils of Citrus limon (L.) Burm.F., (lemon) and Melissa officinalis, (balm) were evaluated against Anopheles stephensi in laboratory on animal and human and compared with synthetic repellent, N,Ndiethyl- 3-methylbenzamide (Deet) as a standard. Results of statistical analysis revealed significant differences between oils and extracts (P< 0.05) against the tested species, thus oils were more effective than extracts. There was no significant difference between Deet and lemon oil, whereas the difference between lemon and melissa oils was significant. Relative efficacy of lemon oil to Deet was 0.88 whereas it was 0.71 for melissa oil. The results were found marginally superior in repellency for animals than human. Due to advantages of botanic compounds to synthetic compounds we recommend lemon essential oil as an effective alternative to Deet with potential as a means of personal protection against mosquito vectors of disease.